Growth of PbSe Quantum Dots Within High‐Index Lead‐Phosphate Glass for Infrared Saturable Absorbers. Issue 1 (7th January 2013) - Kannan, Pradeesh; Choudhary, Amol; Mills, Benjamin; Feng, Xian; Shepherd, David P.; Heo, J.
<x xml:space="preserve">Abstract</x> PbSe quantum dots (QDs) were grown in high‐refractive‐index low‐melting‐temperature lead‐phosphate glass. The lowest energy exciton transition of the QDs was tuned over a wide range within the infrared spectral region (0.93–2.75 μm) by a controlled heat treatment. The measured QD radius ranged between 2 and 5.3 nm, with a time (t) dependence of t0.29 for long dwelling times during the heat treatment, indicating that the QD growth mechanism tends to follow Lifshitz‐Slyozov‐Wagner theory. The QD saturable absorber behavior at 1.2 μm had a measured saturation fluence of ~2.1 μJ/cm2.